Corporate Expropriation From The Perspective Of Ownership Contestability And Board Governance In Malaysia - Hamzah, Ahmad Husni (2018)
This thesis examines the effect of ownership contestability and board governance on corporate expropriation in Malaysia. The objective of the study is to investigate whether the presence of multiple shareholders structure and board governance have significant impact on the corporate expropriation of Malaysian PLCs. Specifically, the study is directed towards identifying the effect of ownership of only controlling shareholder and board governance on corporate expropriation, the effect of ownership contestability between controlling shareholder and large shareholders; and board governance on corporate expropriation and the effect of ownership of only large shareholders and board governance on corporate expropriation.